1996
DOI: 10.1038/bjc.1996.666
|View full text |Cite
|
Sign up to set email alerts
|

CAM 17.1 - A new diagnostic marker in pancreatic cancer

Abstract: CAM 17.1-Ab is a recently described monoclonal antibody that detects a mucus glycoprotein with high specificity for intestinal mucus, particularly in the colon, small intestine, biliary tract and pancreas. We investigated the expression and release of CAM 17.1 in pancreatic carcinoma cell lines and tissue specimens of normal pancreas, chronic pancreatitis and pancreatic cancer. CAM 17.1 was weakly expressed on normal ductal cells and chronic pancreatitis, whereas it was overexpressed in pancreatic cancer. Seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
3

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 27 publications
0
10
0
3
Order By: Relevance
“…CAM 17‐1 shows a sensitivity similar to that of CA 19‐9 but with higher specificity. Thus, in patients with chronic pancreatitis, only 10% had elevated levels of this marker 11…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…CAM 17‐1 shows a sensitivity similar to that of CA 19‐9 but with higher specificity. Thus, in patients with chronic pancreatitis, only 10% had elevated levels of this marker 11…”
mentioning
confidence: 98%
“…However, the sensitivity and specificity of these markers appeared to be insufficient for the differentiation of pancreatic carcinoma and chronic pancreatitis. Recently, a new marker, CAM17‐1, with a high specificity for intestinal mucus, particularly in the colon, small intestine, biliary tract, and pancreas, has been described 11, 12. CAM 17‐1 shows a sensitivity similar to that of CA 19‐9 but with higher specificity.…”
mentioning
confidence: 99%
“…Nevertheless, there are 11 recent studies on CEA which can be detected at low levels in fetal and normal adult tissue while high serum levels indicate presence of pancreatic cancer. The main problem of this biomarker is its low sensitivity of 25-56% at a high specificity of 82-100% for discriminating carcinoma from controls (Duraker et al 2007;Ehmann et al 2007;Gansauge et al 1996;Groblewska et al 2007;Liao et al 2009;Mroczko et al 2009;Ni et al 2005;Pasanen et al 1994;Zhao and Zhang 2008) (Table 1B). The best performance was reported by Ehmann et al (2007) on 96 carcinomas and 96 controls with 56% sensitivity and 82% specificity.…”
Section: Group B: Carcinoembryonic Antigenmentioning
confidence: 96%
“…Recent studies have identified other potential biomarkers for pancreatic cancer, including CA494, 85 carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1), 86 parathyroid hormone-related protein (PTHrP), 87 tumor M2-pyruvate kinase (TuM2-PK), 88 anti-mucin antibody CAM 17.1, 78 and serum beta-human chorionic gonadotropin (β-HCG). 89 Although their performance characteristics in initial studies are promising, larger studies are needed to confirm their clinical applicability and they are currently used only in research settings.…”
Section: Available and Anticipated Tumor Markersmentioning
confidence: 99%